A comprehensive review on microbial l‐asparaginase: Bioprocessing, characterization, and industrial applications. (18th February 2020) - Chand, Subhash; Mahajan, Richi V.; Prasad, Jai Prakash; Sahoo, Debendra K.; Mihooliya, Kanti Nandan; Dhar, Mahesh S.; Sharma, Girish
Abstract: l ‐Asparaginase (E.C.3.5.1.1.) is a vital enzyme that hydrolyzes l ‐asparagine to l ‐aspartic acid and ammonia. This property of l ‐asparaginase inhibits the protein synthesis in cancer cells, making l ‐asparaginase a mainstay of pediatric chemotherapy practices to treat acute lymphoblastic leukemia (ALL) patients. l ‐Asparaginase is also recognized as one of the important food processing agent. The removal of asparagine by l ‐asparaginase leads to the reduction of acrylamide formation in fried food items. l ‐Asparaginase is produced by various organisms including animals, plants, and microorganisms, however, only microorganisms that produce a substantial amount of this enzyme are of commercial significance. The commercial l ‐asparaginase for healthcare applications is chiefly derived from Escherichia coli and Erwinia chrysanthemi . A high rate of hypersensitivity and adverse reactions limits the long‐term clinical use of l ‐asparaginase. Present review provides thorough information on microbial l ‐asparaginase bioprocess optimization including submerged fermentation and solid‐state fermentation for l ‐asparaginase production, downstream purification, its characterization, and issues related to the clinical application including toxicity and hypersensitivity. Here, we have highlighted the bioprocess techniques that can produce improved and economically viable yields of l ‐asparaginase from promising microbial sources in the current scenario where there is an urgent need for alternate l ‐asparaginase with less adverse effects. Abstract : Graphical summary of l ‐asparaginase.